Cartoon Network LP v. CSC Holdings, Inc : Remote-Storage Digital Video Recorders and Copyright Law. (U.S. Congressional Research., 2009)
Reviews Cartoon Network LP v. CSC Holdings, Inc., in which the Court of Appeals for the Second Circuit held that Cablevision's proposed remote-storage digital video recording service did not directly infringe the reproduction or public performance rights of those holding copyrights in the recorded materials. Examines litigation brought against time-shifting technology companies, holdings in the case, and effects of the Cartoon Network decision.